An adaptive cyber-physical system’s approach to construction progress monitoring and control - Olatunji, Oluwole; Akanmu, A. (American Society of Engineers, 2014)
This chapter proposes an approach to deploying an adaptive cyber-physical system (aCPS) for project monitoring and control. In developing the system, we use a prototype platform which employs a radio frequency identification system that is capable of real-time location sensing to track construction processes and resources within spatially mapped activity areas. Data from the system are fed into BIM-based construction models such that project statuses are tracked and aligned with project schedule in an interactive manner. Outcomes of the procedure are primed on the impact of real time status tracking as project stakeholders are able to continuously create quick and preventive solutions against schedule delays and disruptions before overruns occur. Compared to existing project monitoring and control systems, extant approaches are susceptible to the limitations of manual approaches where data gathering and their syntheses are non-adaptive. Our findings also show that, in a data intensive environment as construction, satisfactory project outcomes are driven only by effective interactions between cyber and physical systems. We conclude that, to maximize system deliverables through cross-domain technologies – particularly to swiftly aid decision-making, autonomous systems must be able to shift boundaries dynamically, be context-adaptive and be capable of generating real-time information.